Psychotic Symptoms and Malignant Neuroleptic Syndrome in Williams Syndrome: A Case Report - Karpov, Boris; Muhonen, Maria; Kieseppä, Tuula (Frontiers in Psychiatry, 2022)
Background Somatic and mental comorbidities are characteristic of individuals with Williams syndrome. The psychiatric profile of these patients mainly comprises affective disorders, while psychotic symptoms are rare. Methods We present a case report of psychosis and malignant neuroleptic syndrome in a patient with Williams syndrome. We also conduct a review of recent works on the topic. Case presentation A 38-year-old Caucasian male with Williams syndrome presented with somatic delusions, previously experiencing severe anxiety and concerns about a headache. The patient was prescribed olanzapine, which did not, however, have any effect on the delusions. After switching to lurasidone, the patient presented with malignant neuroleptic syndrome (muscle rigidity, tremor, urinary retention, fluctuating level of consciousness). He was hospitalized and the antipsychotic medication was discontinued. After somatic recovery, the patient did not experience severe anxiety and the somatic delusions diminished notably. The patient was discharged from the hospital in a stable physical condition, albeit still with transient worries about his health condition. Conclusions We present a case of the coincidence of Williams syndrome and psychosis. We hypothesize on the possible pathological relationships between the onset of the psychosis and severe anxiety in an individual with Williams syndrome. This case report duly contributes to the limited literature on psychiatric comorbidity in Williams syndrome.